The Quran's Perspective on Followers of Other Religions Through the Interpretation of Tartīb al-Nuzūl by Abid al-Jabiri - Mu'awwanah, Nafisatul (QOF, 2023)
Literally, the Qur'anic verses that speak about people of other religions are ambivalent. A number of verses in the Qur'an appear to criticize them, but in some other verses, neutrality is evident. To compromise these verses, Abid al-Jabiri considers the necessity of knowledge regarding the logical connection between the Quran and the Prophet's preaching era through reading the Quran based on the tartīb al-nuzūl. This paper is aimed at looking at the verses of the Qur'an that talk about people of other religions based on tartīb al-nuzūl, by involving the development of the historical context of the Prophet's da'wah From the results of the reading, it can be seen that first, the Qur'an does not only criticize other religious communities, but also gives appreciation, or is neutral by positioning them as humans in general. Historically, the verses in the form of criticism in the Makkah era were related to the issue of the creed of Muslims and as an answer to the questions of the people of Makkah about the relationship between Islam and other heavenly religions. While the critical verses that were revealed in the Medina era were more of a Qur'anic response to the morals of certain Medina Jews who betrayed the Prophet which at that time led to division. Secondly, the need to live together in harmony through shared understanding is an unavoidable need in the present. The Qur'an criticizes exclusive attitudes and invites openness in religion in order to avoid division.